1989
DOI: 10.1042/cs0760087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an olive-oil-rich diet on erythrocyte membrane lipid composition and cation transport systems

Abstract: 1. In this study we sought to test the possibility that an olive-oil-rich diet might influence the membrane lipid composition and cation transport mechanisms in erythrocytes. 2. To this end, 11 normotensive normolipidaemic healthy volunteers were given a standard relatively low fat diet (28% of total energy) for 3 weeks, followed by a high fat (38% of total energy), olive-oil (100 g/day)-enriched diet for the 3 subsequent weeks, in a metabolic ward. The two diets contained the same amount of cholesterol (400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…In the first place, although the number of studies is scarce, it seems that a high MUFA intake modifies membrane phospholipids in a way 43,44 that can, in turn, alter BP regulation and lead to lower levels of BP 29 . In fact, a recent study has shown that a molecule derived from oleic acid, 2-hydroxyoleic acid, has an impressive antihypertensive effect 45 .…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…In the first place, although the number of studies is scarce, it seems that a high MUFA intake modifies membrane phospholipids in a way 43,44 that can, in turn, alter BP regulation and lead to lower levels of BP 29 . In fact, a recent study has shown that a molecule derived from oleic acid, 2-hydroxyoleic acid, has an impressive antihypertensive effect 45 .…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Biologically occurring fatty acids have been extensively studied due to their strong link to numerous health benefits [1,2]. Fatty acids, which are found in foods such as fruits, seeds, nuts, vegetable oils, animal fats, and fish oils, can be categorized into saturated, monounsaturated, polyunsaturated, and trans fats.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the composition of biological membranes is influenced by the type of fat present in the diet. Thus, diets rich in oleic acid (OA) (such as the Mediterranean diet) are associated with increased levels of this FA in various plasma membranes of rats and humans (10)(11)(12). Interestingly, changes in membrane levels of OA are accompanied by modulations in the function of various proteins (11,12).…”
mentioning
confidence: 99%